Ourselves and Our Posterity: Essays in Constitutional Originalism - Watson, Bradley C. S. (Lexington Books, 2009)
Arguments over constitutional interpretation increasingly highlight the full range of political, moral, and cultural fault lines in American society. Yet all the contending parties claim fealty to the Constitution. This volume brings together some of America's leading scholars of constitutional originalism to reflect on the nature and significance of various approaches to constitutional interpretation and controversies. Throughout the book, the contributors highlight the moral and political dimensions of constitutional interpretation. In doing so, they bring constitutional interpretation and its attendant disputes down from the clouds, showing their relationship to the concerns of the citizen. In addition to matters of interpretation, the book deals with the proper role of the judiciary in a free society, the relationship of law to politics, and the relationship of constitutional originalism to the deepest concerns of political thought and philosophy.